Lessons Learned for Establishing Hospital Safety Climate with ROI vs Cost Control Approach as a Budget Policy Advocacy - Nurani, Promisetyaningrum Fitria; Siregar, M Arbi; N, Pramadyo Adhi; H, Ria Nuril (Ilmu Bersama Center, 2025)
Objective: The classical issue in most of the Asian countries on establishing hospital safety climate is the lack of budget for safety program due to the management perspective that safety is a burden. It makes safety programs annually only submitted but unapproved because of various management decisions allocating the budget to another program which is considered to be more important. With a lack of budget makes many safety programs are stuck and unimproved. Activity: In the field visit from one of the famous referral hospitals in Yogyakarta, hospital safety climate implementation is reviewed as a picture of hospital safety climate in general. This paper tries to solve the classical issue that inhibits the safety climate implementation in the hospital with a brief introduction to the ROI vs Cost Control for the decision-makers which referenced from various journals as the evidence. Regulation Review: The laws and regulations regarding hospital safety have entered into the legal system that must be fulfilled by the hospital through accreditation at least once every 3 years. However, some of the hospital safety implementations as a major part of the safety climate in hospital runs into unsustain because it is only done as a fulfillment of the obligation to pass accreditation completely which is called